Method for removing sulfur from carbon material
By performing heat treatment and desulfurization treatment in an inert atmosphere, the problem of high sulfur content in biological carbon precursors is solved, and the production of low sulfur content carbon materials and the performance improvement of secondary battery are achieved.
Patent Information
- Application Number
- CN202380039131.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-09
- Filing Date
- 2023-05-09
- Publication Date
- 2024-12-20
AI Technical Summary
The prior art is difficult to effectively remove the problem of high sulfur content in biologically based carbon precursors, resulting in a decrease in the long-term performance and life of carbon materials used in secondary batteries.
By performing heat treatment and desulfurization treatment in an inert atmosphere, sulfur in the carbon material is removed with hydrogen and carbon-containing gas, the sulfur content is controlled to be less than 0.8%, and the carbon material is used as the active material of the negative electrode in a non-aqueous secondary battery.
It realizes the production of carbon materials with low sulfur content at a low cost and scale, improves the Coulomb efficiency and long-term circulation performance of secondary batteries, and avoids structural damage and performance degradation.
Smart Images

Figure CN119173472A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a carbon material with a low sulfur content from a sulfur-containing bio-based carbon precursor. The present invention also relates to a carbon material with a low sulfur content; a negative electrode for a non-aqueous secondary battery comprising the carbon material as an active material; and the use of the carbon material as an active material in a negative electrode of a non-aqueous secondary battery. Background Art
[0002] Secondary batteries, such as lithium-ion batteries, are batteries that can be charged and discharged multiple times, i.e. they are rechargeable batteries. For example, lithium-ion batteries are commonly used today in consumer electronic devices, electric vehicles, and stationary energy storage systems. Lithium-ion batteries have high energy density, high operating voltage, low self-discharge, and low maintenance requirements.
[0003] In lithium-ion batteries, lithium ions flow from the negative electrode through the electrolyte to the positive electrode during discharge and back during charging. Today, lithium compounds, in particular lithium transition metal oxides, such as lithium nickel manganese cobalt oxide, or alternatively lithium iron phosphate are typically used as positive electrode materials, and carbonaceous materials are used as negative electrode materials.
[0004] Graphite (natural or synthetic graphite) is currently used as the negative electrode material for most lithium-ion batteries due to its high energy density and stable charge / discharge performance over time. Alternatives to graphite are amorphous carbon materials, such as hard carbon (non-graphitizable amorphous carbon) and soft carbon (graphitizable amorphous carbon), which lack long-range graphitic order. Amorphous carbon can be used as the sole active electrode material or in a mixture with graphite.
[0005] Hard carbons generally have good charge / discharge rate performance, which is desirable for fast charging devices and high power systems. The electrochemical charge / discharge of hard carbon occurs between 1.3 V relative to Li+ / Li to <0 V relative to Li+ / Li, and includes a stable, sloped potential region above about 0.1 V relative to Li+ / Li and an extended potential plateau region below this value when the electrode potential is plotted against the capacity. The actual capacity of hard carbon can exceed that of graphite, reaching values of 500 mAh / g and above. The average electrode charge / discharge potential relative to Li+ / Li for hard carbon is higher than that for graphite.
[0006] Both graphite and amorphous carbon operate at potential ranges outside the thermodynamic stability window of electrolytes typically used in lithium-ion batteries. During the first charge, the electrolyte decomposes, and part of the decomposition products form a protective layer on the electrode surface, the so-called "solid electrolyte interphase" (SEI). The formation of SEI irreversibly consumes charge, mainly during the first charge, resulting in irreversible capacity in the first (several) cycles and reducing the initial coulombic efficiency. Once the SEI is fully formed, the electrolyte decomposition ends and reversible cycling becomes possible.
[0007] A variety of bio-based materials have been used to prepare amorphous carbon for use in secondary batteries. For example, US2018162733 A1 describes carbonaceous materials derived from coconut shells, and US6143268 A describes carbonaceous materials derived from carbohydrates such as cellulose or sucrose.
[0008] Amorphous carbon can also be derived from lignin, such as described in WO9746314 A1. Lignin is an aromatic polymer, which is the main component in, for example, wood, and is also one of the most abundant carbon sources on Earth. In recent years, with the development and commercialization of the technology of extracting lignin in a highly purified, solid and particularized form from the pulp manufacturing process, it has attracted significant attention as a possible renewable substitute for aromatic chemical precursors currently mainly derived from the petrochemical industry. Amorphous carbon derived from lignin is typically non-graphitizable, i.e., hard carbon. However, hard carbon derived from lignin has also shown the problem of insufficient coulombic efficiency so far.
[0009] Nowadays, the most commercially relevant source of lignin is kraft lignin. This lignin is obtained from hardwood or softwood by the kraft process. The lignin can be separated from alkaline black liquor using, for example, a membrane or ultrafiltration. LignoBoost is a common separation process and is described in, for example, WO2006031175A1. In this process, lignin is precipitated from alkaline black liquor by reducing the pH level, usually by adding carbon dioxide, and then filtered out. In the next step, the lignin filter cake is re-slurried and washed under acidic conditions, usually using sulfuric acid. The precipitated and washed lignin can be used as is or further dried.
[0010] Kraft lignin contains high levels of sulfur due to the use of sulfur-based reagents, such as sodium sulfide, during cooking to promote the breaking of chemical bonds between cellulose and lignin. Sulfur will also be retained in the carbon-rich material derived from kraft lignin, resulting in high residual sulfur levels in the carbon-rich material, typically above 1.0 wt%. When the carbon-rich material is used in a secondary battery, the high sulfur content can cause side reactions during battery cycling and thereby reduce the long-term performance and life of the battery.
[0011] Removing sulfur from kraft lignin by washing is challenging because most of the sulfur in lignin, typically more than 70%, is covalently bonded to the carbon through carbon-sulfur bonds. Therefore, in order to remove sulfur from lignin, what is required is harsh chemical treatments such as alkaline, oxidative or reducing agents. These chemical treatments are not only expensive, but can also cause simultaneous degradation of the lignin structure, leading to quality control issues for the produced lignin. When such lignin is converted to carbon, the resulting carbon can also exhibit structural defects, making such carbon unsuitable for use in batteries.
[0012] Another option is to use lignin with a low initial sulfur content, such as organosolv lignin. However, such materials are typically more expensive than kraft lignin and are therefore less suitable as precursors for the industrial production of carbon materials.
[0013] EP2831182A2 describes the removal of sulfur by alkaline treatment of carbon black. The alkaline chemicals required are expensive and change the pH of the carbon material so that an additional neutralization step may be required. In addition, the structure of the carbon material may be destroyed.
[0014] Thus, there is a need for improved methods for producing carbon materials from sulfur-containing bio-based carbon precursors, wherein the obtained carbon has a low sulfur content and has a sufficiently high initial coulombic efficiency. Summary of the invention
[0015] It is an object of the present invention to provide carbon materials obtained from bio-based carbon precursors, which carbon materials have a sufficiently low sulfur content that they can be used in energy storage applications without any negative impact on the performance of the energy storage device.
[0016] It is a further object of the present invention to provide a method for removing sulfur from a carbon material, wherein the carbon material is obtained from a bio-based carbon precursor.
[0017] It is a further object of the present invention to provide a process for removing sulfur from carbon materials which is cost effective and compatible with large-scale production.
[0018] The above objects and other objects that will be recognized by those skilled in the art based on the present invention are achieved through multiple aspects of the present invention.
[0019] According to a first aspect, the invention relates to a method for producing a carbon material having a sulfur content of less than 0.8% by weight, less than 20 m 2 / g BET specific surface area and less than The average grain size (Lc) in the direction of the c-axis of the present invention is as follows:
[0020] - providing a bio-based carbon precursor, wherein the bio-based carbon precursor has a sulfur content in the range of 1.0 to 5.0 wt. %;
[0021] - subjecting the bio-based carbon precursor to a heat treatment in an inert atmosphere at one or more temperatures ranging from 500° C. to 1500° C., wherein the heat treatment is carried out for a total time of 0.5 to 10 hours, to obtain a carbon material;
[0022] - subjecting the carbon material to a desulfurization treatment in an inert atmosphere comprising hydrogen and / or at least one carbon-containing gas, wherein the desulfurization treatment is carried out at one or more temperatures in the range of 800° C. to 1300° C. for a total period of 10 minutes to 5 hours, so as to remove sulfur from the carbon material and obtain a carbon material having a sulfur content of less than 0.8% by weight;
[0023] Wherein, the desulfurization treatment may optionally be carried out at least partially during the heat treatment.
[0024] According to a first aspect, the method of the present invention is based on the surprising recognition that sulfur can be removed from a carbon material obtained from a sulfur-containing bio-based carbon precursor by a desulfurization treatment carried out in an inert atmosphere comprising hydrogen and / or at least one carbon-containing gas. The method of the present invention avoids the need to remove sulfur from the bio-based carbon precursor and is therefore cost-effective and scalable, enabling its use in large-scale carbon production processes. Furthermore, the need for a desulfurization treatment that could potentially damage the structure of the bio-based carbon precursor is reduced by the method of the present invention.
[0025] According to a second aspect, the present invention relates to a carbon material for a negative electrode of a non-aqueous secondary battery, wherein the carbon material is obtained from a bio-based carbon precursor, the bio-based carbon precursor having a sulfur content in the range of 1.0 to 5.0 wt. %, and wherein the carbon material has a sulfur content of less than 0.8 wt. %; less than 20 m 2 / g BET specific surface area; and less than The average crystallite size (Lc) in the direction of the c-axis. The carbon material according to the second aspect can be obtained by the method according to the first aspect.
[0026] According to a third aspect, the present invention relates to a negative electrode for a non-aqueous secondary battery, the negative electrode comprising, as an active material, a carbon material obtainable by the method according to the first aspect or the carbon material according to the second aspect.
[0027] According to a fourth aspect, the present invention relates to use of a carbon material obtainable by the method according to the first aspect or the carbon material according to the second aspect as an active material in a negative electrode of a non-aqueous secondary battery.
[0028] The carbon material according to the present invention has a low sulfur content of less than 0.8 wt. % and a carbon content of less than 20 m 2 / g BET specific surface area and less than The low sulfur content combined with the values defined for the BET specific surface area and Lc produces a carbon material suitable for use as an active material in the negative electrode of a non-aqueous secondary battery. A non-aqueous secondary battery including the carbon material according to the present invention has desirable properties, such as sufficiently high coulombic efficiency and good long-term cycle performance. DETAILED DESCRIPTION
[0029] The method according to the first aspect of the invention involves the step of providing a bio-based carbon precursor, wherein the bio-based carbon precursor has a sulfur content in the range of 1 to 5 wt%, preferably in the range of 1 to 3 wt%, or 1 to 2 wt%. In one embodiment, the bio-based carbon precursor has a sulfur content of at least 1 wt%. As used herein, the term "bio-based carbon precursor" refers to any sulfur-containing bio-based material that can be converted into a carbon material by thermal treatment. Examples of the bio-based carbon precursor are tall pitch oil and sulfur-containing lignin, such as kraft lignin and lignin sulfonate.
[0030] The sulfur content in the bio-based carbon precursor and in the carbon material can be determined using elemental analysis, such as inductively coupled plasma (ICP) spectroscopy, organic elemental analysis (OEA), and X-ray fluorescence (XRF).
[0031] Preferably, the bio-based carbon precursor is kraft lignin, i.e. lignin obtained by the kraft process. Preferably, the kraft lignin is obtained from hardwood or softwood, most preferably from softwood.
[0032] The kraft lignin can be obtained by using the process disclosed in WO2006031175 A1, generally referred to as the LignoBoost process. Typically, the process involves the following steps: precipitating lignin from alkaline black liquor by acidification; separating the precipitated lignin; re-slurrying the lignin at least once under acidic conditions. The obtained lignin can be dried and pulverized and thus provided as solid particles. The lignin can be further purified before being used in the method according to the present invention. The purification typically results in a purity of the lignin material of at least 90%, preferably at least 95%, more preferably at least 98%, based on the dry weight of the lignin material. Thus, the lignin material used in the process according to the present invention preferably contains less than 10%, preferably less than 5%, more preferably less than 2% of impurities, such as cellulose and inorganic compounds, based on the dry weight of the lignin material. The sulfur content of the obtained lignin is typically in the range of 1 to 5% by weight. The main part of the sulfur present in the lignin is covalently bonded via sulfur-carbon bonds.
[0033] In one embodiment, the kraft lignin is provided in the form of an agglomerated lignin having a particle size distribution such that at least 80% by weight of the agglomerates have a diameter in the range of 0.2 to 5.0 mm.
[0034] In the context of the present invention, if a particle is not spherical, the diameter of the particle is the diameter of the equivalent sphere of the particle. The diameter of the equivalent sphere is the diameter of a sphere of equivalent volume.
[0035] The agglomerated lignin can be obtained by the method described in WO2021250604 A1. In brief, the method comprises compacting lignin powder and crushing the compacted lignin to obtain agglomerated lignin. The agglomerated lignin may have a density of 0.5 g / cm 3 Up to 0.7g / cm 3 , preferably 0.5g / cm 3 Up to 0.6g / cm 3 The bulk density is within the range of .
[0036] The compaction of the lignin is preferably carried out by roller compaction. In the compaction step, an intermediate product is generated. Here, fine lignin powder is usually fed through a hopper and conveyed to a compaction zone by a horizontal or vertical feed screw, where the material is compacted into sheets by a compaction roller with a defined gap. By controlling the speed of the feed screw, the pressure in the compaction zone develops, and a sheet with uniform density can be obtained. The pressure development in the compaction zone can preferably be monitored and controlled by the rotation speed of the compaction roller. When the powder is dragged between the rollers, it enters the so-called roller gap area (niparea, pressure zone area), where the density of the material increases, and the powder is converted into sheets or strips. The roller used has a cavity. The depth of each cavity used in the roller compaction is 0.1mm to 10mm, preferably 1mm to 8mm, more preferably 1mm to 5mm or 1mm to 3mm. The specific pressure applied during the compaction may vary depending on the equipment used for compaction, but may be in the range of 1kN / cm to 100kN / cm. Suitable equipment for carrying out such compaction is known in the art.
[0037] In the crushing step, the intermediate product from the compacting step is subjected to crushing or grinding, for example by a rotary granulator, a cage mill, a beater mill, a hammer mill or a crasher mill and / or a combination thereof. During this step, further intermediate products are generated.
[0038] After crushing, preferably make the crushed material undergo a screening step to remove fine materials.In addition, large materials, such as agglomerates with a diameter greater than 5.0 mm, can also be removed and / or recycled back to the crushing step.
[0039] Providing the kraft lignin in the form of agglomerated lignin is advantageous because the lignin is less prone to melt / swell and change in size during subsequent thermal treatment. In addition, by compacting the lignin powder into agglomerates, dusting during handling of the lignin powder is reduced, thereby avoiding problems such as explosions that can be caused by dust during processing.
[0040] In one embodiment, the bio-based carbon precursor further comprises additives. Any suitable additives, such as binders or lubricants, may be added to facilitate subsequent processing and improve the density and mechanical properties of the bio-based carbon precursor. In addition, additives that have an impact on the properties of the final carbon material, such as functional enhancement additives, may be added. The total amount of the additives is preferably less than 5 wt%, such as less than 2 wt%, based on the total dry weight of the additives and the bio-based carbon precursor.
[0041] The method according to the first aspect of the present invention further comprises the step of subjecting the bio-based carbon precursor to a heat treatment in an inert atmosphere at one or more temperatures in the range of 500°C to 1500°C, wherein the heat treatment is carried out for a total time of 0.5 to 10 hours to obtain the carbon material.
[0042] The term "carbon material" as used herein refers to a non-graphitizable hard carbon material obtained from a bio-based carbon precursor. The carbon material consists essentially of carbon, such that it includes at least 90% by weight carbon, or at least 95% carbon, or at least 99% carbon.
[0043] The term "heat treatment" as used herein refers to the process of heating the bio-based carbon precursor at one or more temperatures and for a sufficient time such that the carbon content of the bio-based carbon precursor increases and such that the bio-based carbon precursor is converted into a carbon material. Depending on the temperature during the heat treatment, different types of carbon materials can be obtained, such as charcoal or hard carbon. In order to obtain hard carbon, a sufficiently high temperature (e.g., at least 1000° C.) must be applied at some point during the heat treatment.
[0044] The heat treatment is performed such that the bio-based carbon precursor is heated to a temperature in the range of 500° C. to 1500° C., preferably 600° C. to 1300° C. The heat treatment is performed for a time period in the range of 0.5 to 10 hours, i.e. the residence time of the bio-based carbon precursor in the apparatus for the heat treatment is in the range of 0.5 to 10 hours.
[0045] The heat treatment may be carried out at the same temperature throughout the heat treatment process, or may be carried out at a varying temperature, for example by gradually increasing the temperature or using a temperature gradient. The heat treatment may include a temperature ramp from a starting temperature to a target temperature. The heating rate may be 1-100°C / minute. For example, the heat treatment may involve several intermediate temperatures with temperature ramps between them before reaching the target temperature required for carbonization of the bio-based carbon precursor. The heat treatment may be carried out in a batch process or a continuous process. Any suitable reactor may be used. The heat treatment is carried out under an inert atmosphere, preferably a nitrogen atmosphere.
[0046] Preferably, the heat treatment comprises a first heating step, preferably followed by a final heating step. The first heating step is preferably carried out at one or more temperatures in the range of 500° C. to 900° C., for example between 500° C. and 700° C., for a period of 0.5 to 5 hours. After the first heating step, the BET specific surface area of the obtained product is typically between 100 and 700 m 2 The BET specific surface area was measured using nitrogen gas.
[0047] The final heating step is preferably carried out at one or more temperatures in the range of 900° C. to 1500° C., for example between 1000° C. and 1300° C., for a period of 10 minutes to 3 hours. After the final heating step at 1000° C. or higher, the BET specific surface area of the obtained product is typically less than 50 m 2 / g, preferably less than 20m 2 The BET specific surface area was measured using nitrogen gas.
[0048] The first and final heating steps may be performed as discrete steps or as a single step in direct sequence. The first and final heating steps may involve heating at one or more temperatures, as discussed above for the thermal treatment. For example, the first heating involves increasing the temperature to about 700°C. The final heating step is preferably performed between 1000°C and 1300°C, for example at about 1000°C.
[0049] The heat treatment can be carried out continuously or in batches. The heating can be carried out using methods known in the art and in an inert atmosphere, such as a nitrogen atmosphere. Preferably, the heating is carried out in a rotary kiln, a moving bed furnace, a pusher furnace or a rotary hearth furnace. If a first heating step and a final heating step are carried out, these steps can be carried out in the same furnace or in different furnaces.
[0050] After the heat treatment, the obtained carbon material has a 2 / g, preferably less than 15m 2 / g, and even more preferably less than 10m 2 The specific surface area is measured using the BET method with nitrogen. For carbon materials to be used in energy storage devices, such as non-aqueous secondary batteries, it is important that their surface area is not higher than about 20 m 2 / g, otherwise the performance of the battery may be impaired. For example, decomposition reactions with the electrolyte may occur, and a decrease in the charge / discharge capacity retention rate. One way to obtain a low surface area is to perform at least one stage of the heat treatment at a temperature of at least 1000°C.
[0051] After the heat treatment, the obtained carbon material has a carbon content of less than Preferably less than The average grain size (Lc) in the direction of the c-axis corresponds to the average total thickness of the carbon layers stacked in the graphite-like region of the carbon. Importantly, the obtained carbon material has a value less than The Lc value of the carbon material is such that the non-aqueous secondary battery using the carbon material in the negative electrode will have good output characteristics, such as charge / discharge performance and low resistance. In one embodiment, the obtained carbon material has to or to A carbon material having an Lc value within a defined range can be obtained by selecting an appropriate temperature during the heat treatment, as known to those skilled in the art.
[0052] The obtained carbon material has a carbon content of 1.4 to 2.1 g / cm 3 The helium true density is in the range of 1.4 to 2.1 g / cm. The helium true density can be determined using a pycnometer, as known to those skilled in the art. It is important to have a helium true density of 1.4 to 2.1 g / cm 3 The helium true density is within the range of , because otherwise when the carbon material is used as an active material in the negative electrode of a non-aqueous secondary battery, the doping and dedoping capabilities of the carbon material may be reduced, and the irreversible capacity of the battery may become larger. If the density of the carbon material is too low, the energy density of the electrode may also be reduced.
[0053] The obtained carbon material may have a hydrogen atom to carbon atom (H / C) ratio of less than 0.01, preferably less than 0.005, as determined by elemental analysis. If the H / C ratio is higher than 0.01, the irreversible capacity of the non-aqueous secondary battery in which the carbon material is used may become larger. Due to the increased aromaticity of the carbon structure, a low H / C ratio is also desired in order to be able to achieve low resistance. The temperature used during the heat treatment can be used to control the H / C ratio.
[0054] The obtained carbon material may have an oxygen atom to carbon atom (O / C) ratio of less than 0.04, preferably less than 0.035, as determined by elemental analysis. If the O / C ratio is higher than 0.04, the irreversible capacity of the non-aqueous secondary battery in which the carbon material is used may become larger. In order to be able to achieve low resistance and good initial coulombic efficiency, a low O / C ratio is also desired.
[0055] Generally, low ratios of both H / C and O / C are desired because this indicates that a large portion of the bio-based carbon precursor has been converted to carbon. When the obtained carbon material is used as an active material in the negative electrode of a non-aqueous secondary battery, the retained hydrogen and oxygen may lead to undesirable reactions, thereby reducing the performance of the battery. The presence of heteroatoms such as hydrogen and oxygen may also interfere with the graphite plane in the graphite-like region of the carbon material and thereby cause defects, which will affect the electrochemical properties of the carbon material.
[0056] Various elemental analysis methods, such as organic elemental analysis (OEA), can be used to determine the H / C ratio and the O / C ratio.
[0057] The obtained carbon material may have a carbon content determined by X-ray diffraction. to within the range of to The average lattice spacing (d 002 ). 002 The value corresponds to the distance between carbon layers in the graphite-like region of the carbon material. 002 The carbon material can be used to construct batteries with good performance, especially in terms of capacity. For the intercalation of ions such as lithium and larger ions such as sodium, what is required is a sufficiently large d 002 value.
[0058] The method according to the first aspect further comprises the following steps: subjecting the obtained carbon material to a desulfurization treatment in an inert atmosphere comprising hydrogen and / or at least one carbon-containing gas, wherein the desulfurization treatment is carried out at one or more temperatures in the range of 800°C to 1200°C, preferably 900°C to 1100°C, for a total time period of 10 minutes to 5 hours, preferably 30 minutes to 3 hours, to remove sulfur from the carbon material and obtain a carbon material having a sulfur content of less than 0.8 weight %.
[0059] As used herein, the term "desulfurization treatment" refers to a gas treatment that removes sulfur from a carbon material, thereby reducing the total amount of sulfur present in the carbon material.
[0060] The term "inert atmosphere" as used herein refers to an oxygen-poor atmosphere. Preferably, the oxygen content in the inert atmosphere is less than 1 volume %, such as less than 0.1 volume %. In one embodiment, during the desulfurization treatment, the inert atmosphere is composed of nitrogen and hydrogen and / or at least one carbon-containing gas.
[0061] The desulfurization process may be carried out at the same temperature throughout the desulfurization process, or may be carried out at varying temperatures, such as by increasing the temperature stepwise or using a temperature gradient. The desulfurization process may include a temperature ramp from a starting temperature to a target temperature. The heating rate may be 1-100° C. / minute. For example, the desulfurization process may involve several intermediate temperatures with temperature ramps between them before reaching the target temperature required for removing sulfur.
[0062] The desulfurization treatment is carried out for a total time period of 10 minutes to 5 hours. In this case, the total time period refers to the total time that the carbon material is in contact with hydrogen and / or at least one carbon-containing gas in the reactor, or the total time during which hydrogen and / or at least one carbon-containing gas is supplied to the reactor.
[0063] The desulfurization treatment may be performed using both hydrogen and at least one carbon-containing gas, or using only hydrogen, or using only at least one carbon-containing gas. In one embodiment, the desulfurization is performed at least partially simultaneously using hydrogen and at least one carbon-containing gas. In one embodiment, the desulfurization treatment is performed using hydrogen followed by the addition of at least one carbon-containing gas. In one embodiment, the desulfurization treatment is performed first using hydrogen and then using at least one carbon-containing gas in separate steps.
[0064] In one embodiment, during the desulfurization treatment, the total amount of hydrogen and / or the at least one carbon-containing gas is in the range of 5 to 30 volume %. The term "total amount" as used herein refers to the sum of the amount of hydrogen present inside the reactor and the amount of the at least one carbon-containing gas used for the desulfurization treatment. In one embodiment, the desulfurization treatment is carried out in an inert atmosphere, the inert atmosphere comprising nitrogen in the range of 70 to 95 volume % and hydrogen and / or the at least one carbon-containing gas in the range of 5 to 30 volume %. In one embodiment, the desulfurization treatment is carried out in an inert atmosphere, the inert atmosphere comprising nitrogen in the range of 70 to 95 volume % and hydrogen in the range of 5 to 30 volume %. In one embodiment, the desulfurization treatment is carried out in an inert atmosphere, the inert atmosphere comprising nitrogen in the range of 80 to 95 volume % and at least one carbon-containing gas in the range of 5 to 20 volume %. In one embodiment, the concentration of hydrogen and / or the at least one carbon-containing gas remains the same during the entire desulfurization treatment. In one embodiment, the concentration of hydrogen and / or the at least one carbon-containing gas varies during the desulfurization treatment, such that the concentration increases or decreases during the desulfurization. Hydrogen or the at least one carbon-containing gas may be supplied to the reactor together with an inert gas, or as a separate stream. Preferably, hydrogen or the at least one carbon-containing gas is supplied as a separate stream for improved control of the supply. Hydrogen or the at least one carbon-containing gas is preferably mixed with an inert gas, such as nitrogen, even when supplied as a separate stream.
[0065] In an alternative embodiment, during the desulfurization treatment, the total amount of hydrogen and / or the at least one carbon-containing gas is in the range of 5 to 60 volume %, such as in the range of 20 to 45 volume % or 30 to 40 volume %. For example, the desulfurization treatment can be carried out in an inert atmosphere comprising nitrogen in the range of 60 to 70 volume % and hydrogen in the range of 30 to 40 volume %.
[0066] As used herein, the term "carbon-containing gas" refers to any carbon-containing compound in gaseous form or which can be volatilized into a gas. In one embodiment, the at least one carbon-containing gas has the general structure C x H y , and preferably the number of carbon atoms is in the range of 1 to 4, and the number of hydrogen atoms is in the range of 2 to 8. In one embodiment, the at least one carbon-containing gas is selected from at least one of methane, ethane, propane, methane, ethylene, propylene, acetylene and methylacetylene. In a preferred embodiment, the at least one carbon-containing gas is selected from acetylene and ethylene. As will be appreciated by those skilled in the art, the temperature during the desulfurization step may have to be adjusted depending on the type of carbon-containing gas used.
[0067] In some embodiments, only one carbon-containing gas is used for the desulfurization process. In a preferred embodiment, the carbon-containing gas is selected from acetylene or ethylene.
[0068] In some embodiments, more than one carbon-containing gas is used for the desulfurization process. In a preferred embodiment using two carbon-containing gases, the carbon-containing gases are acetylene and ethylene.
[0069] In some embodiments, hydrogen and a carbon-containing gas are used for the desulfurization process. In preferred embodiments using both hydrogen and a carbon-containing gas, the carbon-containing gas is selected from methane or ethane.
[0070] In embodiments in which at least one carbon-containing gas is used for the desulfurization process, the desulfurization process may also result in the carbon material being coated with a carbon coating. Whether a coating is obtained depends on parameters such as the concentration and temperature of the at least one carbon-containing gas. Typically, a high concentration of the at least one carbon-containing gas and a high temperature are required for depositing a carbon coating on the carbon material. If a carbon-coated carbon material is desired, the desulfurization process using a carbon-containing gas may be performed at least partially during a coating step, such as during a chemical vapor deposition (CVD) process.
[0071] In one embodiment, the desulfurization treatment is at least partially performed during the thermal treatment. In one embodiment, the entire desulfurization treatment is performed during the thermal treatment. In one embodiment, the desulfurization treatment is at least partially performed during the final heating step. By performing the desulfurization treatment at least partially during the thermal treatment, a more efficient process can be achieved because fewer heating steps are required.
[0072] If the desulfurization treatment is carried out entirely during the heat treatment, the total time of the heat treatment may be longer than the total time of the desulfurization. Preferably, the desulfurization treatment starts (by supplying hydrogen or at least one carbon-containing gas) when the temperature reaches at least 800°C. The heat treatment may also be continued after the desulfurization treatment has been stopped.
[0073] In one embodiment, the entire desulfurization treatment is performed after the heat treatment. In this embodiment, the desulfurization treatment may first heat the carbon to a temperature of at least 800° C. for a period of 0.5 to 2 hours in an inert atmosphere before applying hydrogen and / or at least one carbon-containing gas. The heating ensures that the carbon material has a sufficient temperature when the treatment by hydrogen and / or at least one carbon-containing gas begins. After the desulfurization treatment, the carbon material may also be cooled in an inert atmosphere.
[0074] In one embodiment, the desulfurization treatment comprises a first desulfurization step and a second desulfurization step. One or both of the first or second desulfurization steps may be performed at least partially during the thermal treatment. Parameters such as temperature, time, and concentration and composition of gas used during the desulfurization treatment may be the same or vary between different desulfurization steps. By optimizing such parameters, more efficient removal of sulfur from the carbon material may be achieved. By performing the desulfurization treatment in two steps, more efficient removal of sulfur may be achieved.
[0075] The first and second desulfurization steps may be performed as discrete steps or as a single step in direct sequence.The temperature during the first and final heating steps may be the same or may vary as described above for the desulfurization treatment.
[0076] In one embodiment, the first desulfurization step is performed during the heat treatment. In one embodiment, the first desulfurization step is performed in an inert atmosphere including hydrogen. The amount of hydrogen in the first desulfurization step may be in the range of 5 to 30 volume %. The first desulfurization step may be performed at a temperature in the range of 800°C to 1300°C for a total time period in the range of 10 minutes to 3 hours. In one embodiment, the first desulfurization step is performed during the final heating step. By performing the first desulfurization step during the final heating step, a more efficient process is achieved due to the reduction in the number of process steps. As described above, for the desulfurization treatment, the total time of the final heating step may be longer than the total time of the first desulfurization step.
[0077] In one embodiment, the second desulfurization step is performed in a separate step after the heat treatment. In this embodiment, the second desulfurization step may first heat the carbon to a temperature of at least 800° C. for a period of 0.5 to 2 hours in an inert atmosphere before applying hydrogen and / or at least one carbon-containing gas. The heating ensures that the carbon material has a sufficient temperature at the beginning of the treatment by hydrogen and / or at least one carbon-containing gas. After the second desulfurization step, the carbon material may also be cooled in an inert atmosphere.
[0078] In one embodiment, the second desulfurization step is performed in an inert atmosphere comprising at least one carbon-containing gas. The amount of the at least one carbon-containing gas may be between 5 and 20 volume %. The second desulfurization step may be performed at a temperature in the range of 800° C. to 1100° C. for a total time period of 10 minutes to 3 hours. The second desulfurization may be performed during CVD coating of the carbon material. By performing two desulfurization steps, more efficient sulfur removal may be achieved.
[0079] In one embodiment, the desulfurization treatment comprises: a first desulfurization step, which is carried out in an inert atmosphere including hydrogen and during the final heating step; and a second desulfurization step, which is carried out in an inert atmosphere including at least one carbon-containing gas and after the heat treatment, preferably during CVD coating. By carrying out the first desulfurization step in an atmosphere including hydrogen, the temperature and time can be optimized so that the removal of sulfur is more effective. Due to the different properties of hydrogen and the at least one carbon-containing gas, different temperatures and times are suitable for optimizing the removal of sulfur in different atmospheres. Therefore, in some embodiments, it is advantageous to carry out the desulfurization treatment in two steps, using hydrogen in the first step and at least one carbon-containing gas in the second step. In addition, by supplying only carbon-containing gas in the second step, excessive smoke formation is prevented.
[0080] The desulfurization treatment may be carried out continuously or in batches. Any suitable reactor may be used. Preferably, the desulfurization treatment is carried out in a rotary kiln, a moving bed furnace, a fluidized bed, a pusher furnace or a rotary hearth furnace. If a first desulfurization step and a second desulfurization step are carried out, these steps may be carried out in the same furnace or in different furnaces.
[0081] Sulfur is removed from the carbon material by the desulfurization treatment. It is believed that the desulfurization treatment causes the formation of hydrogen sulfide or carbon disulfide or other volatile sulfur compounds. Due to its volatility, these compounds will not be retained in the carbon. After the desulfurization treatment, the carbon obtained has a sulfur content less than 0.8 weight %, for example, less than 0.7 weight %, or less than 0.5 weight %, or less than 0.3 weight %. In one embodiment, the carbon obtained has a sulfur content in the range of 0 to 0.8 weight %, for example, 0 to 0.7 weight %, or 0 to 0.5 weight %, or 0 to 0.3 weight %. In one embodiment, the carbon obtained has a sulfur content in the range of 0.01 to 0.8 weight %, for example, 0.01 to 0.7 weight %, or 0.01 to 0.5 weight %, or 0.01 to 0.3 weight %. In one embodiment, the carbon obtained has a sulfur content in the range of 0.1 to 0.8 wt%, such as 0.1 to 0.7 wt%, or 0.1 to 0.5 wt%, or 0.1 to 0.3 wt%.
[0082] In one embodiment, wherein the desulfurization treatment is carried out in an inert atmosphere comprising at least one carbon-containing gas, the carbon material obtained after the desulfurization treatment has a carbon content of less than 5 m 2 / g BET specific surface area (measured by nitrogen) and between 1.4 and 1.8 g / cm 3 In one embodiment, no carbonaceous gas is used during the desulfurization process, and the carbon material instead has a helium true density of less than 20 m 2 / g BET specific surface area (measured by nitrogen) and in the range of 1.4 to 2.1 g / cm 3 Regardless of the gas used during the desulfurization process, the desulfurization process has a significant effect on the Lc value, d 002 The O / C ratio or the H / C ratio typically do not have any significant effect. Therefore, after the desulfurization treatment, these parameters remain within the same ranges as those defined for the carbon material obtained after the thermal treatment. The O / C ratio is typically slightly reduced by the desulfurization treatment, especially when at least one carbon-containing gas is used for the desulfurization treatment.
[0083] In one embodiment, the method according to the first aspect of the invention comprises the further step of preheating the bio-based carbon precursor to a temperature in the range of 180°C to 250°C for a period of at least 0.5 hours in an oxidizing atmosphere, wherein the preheating is performed prior to the heat treatment.
[0084] Preheating is performed so that the bio-based carbon precursor is heated to a temperature in the range of 180°C to 250°C, preferably in the range of 180°C to 230°C. The preheating is performed for at least 30 minutes, i.e. the residence time of the bio-based carbon precursor in the device for the preheating is at least 30 minutes. In one embodiment, the preheating is performed for at least 1 hour, or at least 1.5 hours. Preferably, the preheating is performed for less than 12 hours, or less than 6 hours. The preheating may be performed at the same temperature throughout the preheating stage, or may be performed at a varying temperature, for example by gradually increasing the temperature or using a temperature gradient. More preferably, the preheating is performed so that the bio-based carbon precursor is first heated to a temperature in the range of 140°C to 175°C for a period of at least 15 minutes and then heated to a temperature in the range of 175°C to 250°C for at least 15 minutes.
[0085] The step of preheating the bio-based carbon precursor can be performed continuously or in batches. The preheating can be performed using methods known in the art and is performed in an oxidizing atmosphere such as air. Oxygen is required due to the low temperatures used during the preheating. Preferably, the preheating is performed in a rotary kiln, a moving bed furnace or a rotary hearth furnace.
[0086] In the embodiment where the bio-based carbon precursor is lignin, the thermal stability of the lignin is improved by performing a preheating step, so that thermally stable lignin is obtained. In particular, the processability of the lignin is improved in terms of avoiding melting / swelling and maintaining shape and size during subsequent heat treatment by the preheating step.
[0087] In one embodiment, the method further comprises the step of pulverizing the carbon material to obtain a carbon material having an average particle size (D V50 ) of pulverized carbon material. When using carbon material as an active material in the negative electrode of a non-aqueous secondary battery, it is important that the average particle size is not too large, otherwise the charging and discharging speed may be too slow. On the other hand, if the average particle size is too small, the surface area will increase. This will have a negative impact on the battery properties, such as capacity and reactivity with the electrolyte. The average particle size (D V50 ) can be determined using, for example, laser diffraction.
[0088] The comminution can be carried out by any method known in the art. Some examples include cutting mills, blade mixers, ball mills, impact mills, hammer mills and / or jet mills. Optionally, the comminution can be followed by fine / coarse particle selection by classification and / or screening.
[0089] In the embodiment where the heat treatment includes a first heating step and a final heating step, the pulverizing step may be performed after the first heating step or after the final heating step. The pulverizing may be performed before the desulfurization treatment or after the desulfurization treatment.
[0090] After heat treatment and desulfurization, the obtained carbon material can undergo further processing, such as carbon coating by chemical vapor deposition (CVD), pitch coating, thermal and / or chemical purification (in addition to desulfurization), further heat treatment, particle size adjustment and blending with other electrode materials to further improve its electrochemical properties.
[0091] The carbon material obtained by the method according to the first aspect is preferably used as an active material in the negative electrode of a non-aqueous secondary battery (e.g., a lithium ion battery). Due to the low sulfur content of the carbon material used as the active material in the negative electrode, the long-term performance and life of the non-aqueous secondary battery are improved. In addition, the coulombic efficiency is sufficiently high.
[0092] When the carbon material obtained by the method according to the first aspect is used to produce a negative electrode, any suitable method can be used to form such a negative electrode. In the formation of the negative electrode, the carbon-rich material can be processed together with other components. Such other components may include, for example, one or more adhesives to form the carbon material into an electrode, a conductive material such as carbon black, carbon nanotubes or metal powder, and / or other Li storage materials such as graphite or lithium. For example, the adhesive may be selected from but is not limited to poly (vinylidene fluoride), poly (tetrafluoroethylene), carboxymethyl cellulose, natural butadiene rubber, synthetic butadiene rubber, polyacrylate, poly (acrylic acid), algae salt, etc. or a combination thereof. Optionally, a solvent such as 1-methyl-2-pyrrolidone, 1-ethyl-2-pyrrolidone, water or acetone is used during the processing.
[0093] According to a second aspect, the present invention relates to a carbon material for a negative electrode of a non-aqueous secondary battery, wherein the carbon material is obtained from a bio-based carbon precursor, the bio-based carbon precursor having a sulfur content in the range of 1.0 to 5.0 wt. %, and wherein the carbon material has a sulfur content of less than 0.8 wt. %; less than 20 m 2 / g BET specific surface area; and less than The average grain size (Lc) in the direction of the c-axis. The carbon material according to the second aspect can be obtained by the method according to the first aspect. The carbon material according to the second aspect is suitable for use as an active material in the negative electrode of a non-aqueous secondary battery due to its low sulfur content. The carbon material according to the second aspect can be further defined as explained above with reference to the first aspect.
[0094] According to a third aspect, the present invention relates to a negative electrode for a non-aqueous secondary battery, the negative electrode comprising a carbon material obtainable by the method according to the first aspect or the carbon material according to the second aspect as an active material. The negative electrode according to the third aspect may be further defined as explained above with reference to the first aspect.
[0095] According to a fourth aspect, the present invention relates to the use of a carbon material obtainable by the method according to the first aspect or the carbon material according to the second aspect as an active material in a negative electrode of a non-aqueous secondary battery. The negative electrode according to the fourth aspect may be further defined as explained above with reference to the first aspect.
[0096] Example
[0097] Example 1
[0098] Kraft lignin powder obtained by the LignoBoost process and having a sulfur content of 2% by weight was heat treated to obtain a carbon material. The heat treatment was carried out in a nitrogen atmosphere by first heating at 500°C and then by increasing upwards to a final temperature of 1000°C. The obtained carbon material was allowed to cool to room temperature before being crushed to an average particle size of 15 μm using a jet mill. A desulfurization treatment was carried out in a rotary kiln by initial heating at 1050°C for 1 hour in a nitrogen atmosphere, followed by reducing the temperature to 900°C and changing the atmosphere to 25% by volume of acetylene (and 75% by volume of nitrogen). The heating was maintained for 2 hours, after which the gas atmosphere was changed to nitrogen and the carbon material was cooled to room temperature.
[0099] Example 2
[0100] Kraft lignin powder obtained by the LignoBoost process and having a sulfur content of 2% by weight was heat treated to obtain a carbon material. The heat treatment was carried out in a nitrogen atmosphere first at 500°C and then by increasing upwards to a final temperature of 1000°C. The carbon material obtained was allowed to cool to room temperature before being pulverized to an average particle size of 10 μm using a jet mill. A desulfurization treatment was carried out in a fluidized bed reactor at 900°C for 2 hours in a nitrogen atmosphere comprising 5% of hydrogen. After the desulfurization, the carbon material was cooled to room temperature under a nitrogen atmosphere.
[0101] Example 3
[0102] Kraft lignin powder obtained by the LignoBoost process and having a sulfur content of 2% by weight was heat treated to obtain a carbon material. The heat treatment was first carried out at 500°C. The obtained carbon material was allowed to cool to room temperature before being crushed to an average particle size of 10 μm using a jet mill. A desulfurization treatment was carried out in a rotary kiln reactor at 1050°C for 2 hours in a nitrogen atmosphere comprising 40% of hydrogen. After the desulfurization, the carbon material was cooled to room temperature under a nitrogen atmosphere.
[0103] Example 4 - Comparison
[0104] The carbon material was produced as outlined for Example 1 above, except that the desulfurization treatment was omitted.
[0105] The carbon materials obtained in Examples 1-4 were analyzed, and the results are shown in Table 1. BET specific surface area was measured using nitrogen. True density was measured using a densimeter by helium. Sulfur content, H / C ratio, and O / C ratio were determined using flash combustion using organic element analysis. Lc value and d were determined using wide angle X-ray diffraction. 002 value.
[0106] Example 5
[0107] In this example, an electrode was prepared from the carbon material powder obtained in Examples 1, 2 and 4. The electrode was prepared as follows: 82 wt% of carbon powder was mixed with 8 wt% of a poly(vinylidene fluoride) binder dissolved in 1-methyl-2-pyrrolidone, the mixture was coated on a Cu foil via a doctor blade process and dried. A laboratory-type three-electrode cell was constructed from carbon electrodes using a glass fiber separator and 1M LiPF6 dissolved in ethylene carbonate: dimethyl carbonate (1:1 by weight) as an electrolyte, each cell comprising a carbon electrode, a Li metal counter electrode and a Li metal reference electrode. The cell was charged and discharged at a constant current between 0mV relative to Li / Li and 1.5V relative to Li / Li, using a specific current of 74.4mA / g(AM), where g(AM) represents the mass of the active material in the electrode. The charge and discharge capacity and initial coulombic efficiency were evaluated. The results of the carbon materials obtained from Examples 1, 2 and 4 are summarized in Table 1.
[0108] Table 1
[0109]
[0110] In view of the above detailed description of the invention, other modifications and variations will become apparent to those skilled in the art. However, it should be apparent that such other modifications and variations can be implemented without departing from the spirit and scope of the invention.
Claims
1. A method for producing a carbon material having a sulfur content of less than 0.8% by weight, less than 20 m 2 / g BET specific surface area and less than The average grain size (Lc) in the direction of the c-axis, wherein the method The following steps are involved: - providing a bio-based carbon precursor, wherein the bio-based carbon precursor has a sulfur content in the range of 1.0 to 5.0 wt. %; - subjecting the bio-based carbon precursor to a heat treatment in an inert atmosphere at one or more temperatures ranging from 500° C. to 1500° C., wherein the heat treatment is carried out for a total time of 0.5 to 10 hours, to obtain a carbon material; - subjecting the carbon material to a desulfurization treatment in an inert atmosphere comprising hydrogen and / or at least one carbon-containing gas, wherein the desulfurization treatment is carried out at one or more temperatures in the range of 800° C. to 1300° C. for a total period of 10 minutes to 5 hours, so as to remove sulfur from the carbon material and obtain a carbon material having a sulfur content of less than 0.8% by weight; Wherein, the desulfurization treatment may optionally be carried out at least partially during the heat treatment.
2. The method of claim 1, wherein the bio-based carbon precursor is kraft lignin.
3. The method according to claim 2, wherein the kraft lignin is provided in the form of agglomerated lignin having a particle size distribution such that at least 80% by weight of the agglomerates have a diameter in the range of 0.2 to 5.0 mm.
4. The method according to any one of claims 1 to 3, wherein the method further comprises The following steps are involved: - preheating said bio-based carbon precursor to a temperature in the range of 180°C to 250°C for a period of at least 30 minutes in an oxidizing atmosphere, and wherein said preheating step is performed prior to said heat treatment.
5. The method according to any one of claims 1 to 4, wherein the method further comprises The following steps are involved: - pulverizing the carbon material to obtain a particle size having an average particle size (D) in the range of 5 μm to 25 μm v50 ) of crushed carbon material.
6. The method according to any one of claims 1 to 5, wherein the desulfurization treatment comprises a first desulfurization step and a second desulfurization step.
7. The method of claim 6, wherein the first desulfurization step is performed during the thermal treatment.
8. The method according to any one of claims 6-7, wherein the first desulfurization treatment is carried out in an inert atmosphere including hydrogen.
9. The method of claim 8, wherein the first desulfurization step is performed at one or more temperatures in the range of 800°C to 1300°C for a period in the range of 10 minutes to 3 hours.
10. The method according to any one of claims 6 to 9, wherein the second desulfurization step is performed in a separate step after the heat treatment.
11. The method according to any one of claims 6 to 10, wherein the second desulfurization step is performed in an inert atmosphere comprising the at least one carbon-containing gas.
12. The method of claim 11, wherein the second desulfurization step is performed at one or more temperatures in the range of 800°C to 1100°C for a time period in the range of 10 minutes to 3 hours.
13. The method according to any one of claims 1 to 12, wherein the heat treatment comprises a first heating step followed by a final heating step.
14. The method of claim 13, wherein the first heating step is performed at one or more temperatures in the range of 500°C to 900°C for a time period in the range of 0.5 to 5 hours.
15. The method according to any one of claims 13-14, wherein the final heating step is carried out at one or more temperatures in the range of 900°C to 1500°C for a time period in the range of 10 minutes to 3 hours.
16. The method according to any one of claims 13 to 15, wherein a pulverizing step may be performed after the first heating step or after the final heating step.
17. The method according to any one of claims 13 to 16, wherein the desulfurization treatment is at least partially carried out during the final heating step.
18. The method of claim 17, wherein the first desulfurization step is performed during the final heating step.
19. A carbon material for a negative electrode of a non-aqueous secondary battery, wherein the carbon material is derived from a bio-based carbon precursor having a sulfur content in the range of 1.0 to 5.0 wt %, and wherein the carbon material has a sulfur content of less than 0.8 wt %; less than 20 m 2 / g BET specific surface area; and less than The average grain size (Lc) in the direction of the c-axis.
20. The carbon material according to claim 19, wherein the carbon material has an average particle size (D v50 ).
21. The carbon material according to any one of claims 19 to 20, wherein the carbon material has a carbon content of 1.4 to 2.1 g / cm 3 The true density of helium is in the range of .
22. The carbon material of any one of claims 19-21, wherein the carbon material has a hydrogen atom to carbon atom (H / C) ratio of less than 0.01 as determined by elemental analysis.
23. The carbon material of any one of claims 19-22, wherein the carbon material has an oxygen atom to carbon atom (O / C) ratio of less than 0.04 as determined by elemental analysis.
24. The carbon material according to any one of claims 19 to 23, wherein the carbon material has a carbon content of to The average lattice spacing (d 002 ).
25. The carbon material of any one of claims 19-24, wherein the bio-based carbon precursor is kraft lignin.
26. A negative electrode for a non-aqueous secondary battery, comprising a carbon material obtainable by the method according to any one of claims 1 to 18 or a carbon material according to any one of claims 19 to 25 as an active material.
27. Use of a carbon material obtainable by a method according to any one of claims 1 to 18 or a carbon material according to any one of claims 19 to 25 as an active material in a negative electrode of a non-aqueous secondary battery.
Citation Information
Cited By
Carbon material and preparation method and system thereof
CN120622454A
Carbon material, and method and system for producing the same
CN120622454B
